Atenção farmacêutica no uso racional de medicamentos como estratégia na promoção da saúde aos grupos pediátricos e geriátricos: Uma revisão integrativa - Silva Júnior, Josué Arruda da (Brasil, 2019)
This is an integrative review of the literature that sought to highlight and discuss the main characteristics of the pharmaceutical care concept and the Rational Use of Medications, as a tool to promote the health of pediatric and geriatric patients, from scientific publications in the area of pharmacy indexed in the databases of Scielo (Scientific Electronic Library Online), Lilacs (Latin American and Caribbean Literature in Health Sciences) and Capes Journal Portal, using only articles written in Portuguese, between the period of 2009 -2019. Following the inclusion and exclusion criteria, 10 studies were selected for the analysis, of which 50% were published evidencing professional pharmaceutical practice with the age group of children and 50% were published addressing aspects related to the group of elderly people theme. The pharmacist is the professional qualified and qualified to follow, advise and orient properly on the RUM, being this the basic tool used to promote health education activities, aiming to improve the quality of life and success of pharmacological therapy, discuss good practices to establish a relationship of empathy with the minor, ensuring understanding of pharmacological treatment, encouraging healthy living habits to prevent future diseases, warning about self-medication, and stimulating critical thinking about the correct use of medications. drugs, from the process of acquisition and administration of several therapeutic classes. Several articles have proven that the pharmacist is the key to be seen and accepted by the population as the responsible for the drug and raise health care and extend the life expectancy of patients in a healthy way.